Consensus statement by the American Association of Clinical Endocrinology (AACE) and the American Head and Neck Society Endocrine Surgery Section (AHNS‐ES) on Pediatric Benign and Malignant Thyroid Surgery. Issue 4 (1st January 2021) - Stack, Brendan C.; Twining, Christine; Rastatter, Jeff; Angelos, Peter; Baloch, Zubair; Diercks, Gillian; Faquin, William; Kazahaya, Ken; Rivkees, Scott; Sheyn, Tony; Shin, Jennifer J.; Smith, Jessica; et al.
Abstract: Objectives: To provide a clinical disease state review of recent relevant literature and to generate expert consensus statements regarding the breadth of pediatric thyroid cancer diagnosis and care, with an emphasis on thyroid surgery. To generate expert statements to educate pediatric practitioners on the state‐of‐the‐art practices and the value of surgical experience in the management of this unusual and challenging disease in children. Methods: A literature search was conducted and statements were constructed and subjected to a modified Delphi process to measure the consensus of the expert author panel. The wording of statements, voting tabulation, and statistical analysis were overseen by a Delphi expert (J.J.S.). Results: Twenty‐five consensus statements were created and subjected to a modified Delphi analysis to measure the strength of consensus of the expert author panel. All statements reached a level of consensus, and the majority of statements reached the highest level of consensus. Conclusion: Pediatric thyroid cancer has many unique nuances, such as bulky cervical adenopathy on presentation, an increased incidence of diffuse sclerosing variant, and a longer potential lifespan to endure potential complications from treatment. Complications can be a burden to parents and patients alike. We suggest that optimal outcomes and decreased morbidity will come from the use of advanced imaging, diagnostic testing, and neural monitoring of patients treated at high‐volume centers by high‐volume surgeons.